1983
DOI: 10.1073/pnas.80.8.2211
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of the pro-opiomelanocortin mRNA levels in rat pituitary by dopaminergic compounds.

Abstract: Dopamine-containing neurons directly innervate the intermediate lobe of the pituitary and dopaminergic compounds exert inhibitory effects on the secretion and the content of a-melanocyte-stimulating hormone and P-endorphin in this tis-sue. In this study, we have investigated the effects of dopamine receptor agonists and antagonists on the level of pro-opiomelanocortin (POMG) mRNA in rat pituitary. RNAs isolated from neurointermediate pituitary (NIP) or anterior pituitary were spotted on nitrocellulose filters … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
52
0
2

Year Published

1984
1984
1993
1993

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(64 citation statements)
references
References 27 publications
9
52
0
2
Order By: Relevance
“…This is consistent with in vivo studies in which ergocryptine has been shown to decrease the concentration of POMC mRNA [16] and the level of intracellular ,&endorphin immunoreactivity [ 171 in the pars intermedia. In the presence of the dopaminergic agents, however, the reduced rates of POMC synthesis are accompanied by reduced rates of secretion and the ,&endorphin-related peptides remaining in the cells may be more exposed to enzyme modulation, resulting in increased proteolysis and acetylation.…”
Section: Discussionsupporting
confidence: 90%
“…This is consistent with in vivo studies in which ergocryptine has been shown to decrease the concentration of POMC mRNA [16] and the level of intracellular ,&endorphin immunoreactivity [ 171 in the pars intermedia. In the presence of the dopaminergic agents, however, the reduced rates of POMC synthesis are accompanied by reduced rates of secretion and the ,&endorphin-related peptides remaining in the cells may be more exposed to enzyme modulation, resulting in increased proteolysis and acetylation.…”
Section: Discussionsupporting
confidence: 90%
“…The observation that the treatments caused parallel changes in content and release, indicates that they had affected the synthesis of endorphins as well as the release, which is in line with many reports (16,17,19,20,23).…”
Section: Discussionsupporting
confidence: 90%
“…Roberts, Mt. Sinai School of Medicine; see Chen et al 1983). Pit-1 RNA probes were synthesized from pBluescript SK-based vectors (Stratagene).…”
Section: Histochemistrymentioning
confidence: 99%